2022
DOI: 10.3390/molecules27227717
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Antioxidant Properties of Ischnoderma Resinosum Polysaccharide

Abstract: A predominant polysaccharide isolated from Ischnoderma resinosum underwent evaluation for its capacity to scavenge free radicals and its potential antioxidant properties at a cellular-oriented level. This proved that Ischnoderma resinosum polysaccharide (IRP) remarkably curtailed AAPH-induced erythrocyte hemolysis through the inhibition of the generation of ROS (p < 0.05). Rather, it caused the restoration of intracellular antioxidant enzyme (SOD, GSH-Px, and CAT) activities at an acceptable pace and the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…A dose‐dependent decrease in HaCaT cell viability was previously reported in HaCaT cells exposed to H 2 O 2 (100–500 μM) for 12 h, by MTT assay, with a 50% cell mortality at the concentration of 350 μM H 2 O 2 (Zhang et al, 2020), whereas a survival rate of about 60% was reported by Park et al (2020) for HaCaT cells exposed to 500 μM H 2 O 2 for 24 h. In our study, the H 2 O 2 cytotoxic effect was also confirmed by microscopic observation, which allowed to assess the presence of apoptotic features and decreased cell density. Similar morphological alterations were observed in other cell types exposed to H 2 O 2 ‐damage, such as human umbilical vein endothelial cells, neuroblastoma cell line SK‐N‐MC, and HepG2 cells (Bayati et al, 2011; Farshori et al, 2021; Liao et al, 2022). Pre‐treatment with arzanol preserved HaCaT cells from H 2 O 2 cytotoxicity, and significant greater cell viability was observed in arzanol‐treated cells in comparison with those no‐treated exposed to the highest concentrations of oxidants.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…A dose‐dependent decrease in HaCaT cell viability was previously reported in HaCaT cells exposed to H 2 O 2 (100–500 μM) for 12 h, by MTT assay, with a 50% cell mortality at the concentration of 350 μM H 2 O 2 (Zhang et al, 2020), whereas a survival rate of about 60% was reported by Park et al (2020) for HaCaT cells exposed to 500 μM H 2 O 2 for 24 h. In our study, the H 2 O 2 cytotoxic effect was also confirmed by microscopic observation, which allowed to assess the presence of apoptotic features and decreased cell density. Similar morphological alterations were observed in other cell types exposed to H 2 O 2 ‐damage, such as human umbilical vein endothelial cells, neuroblastoma cell line SK‐N‐MC, and HepG2 cells (Bayati et al, 2011; Farshori et al, 2021; Liao et al, 2022). Pre‐treatment with arzanol preserved HaCaT cells from H 2 O 2 cytotoxicity, and significant greater cell viability was observed in arzanol‐treated cells in comparison with those no‐treated exposed to the highest concentrations of oxidants.…”
Section: Discussionsupporting
confidence: 65%
“…A dose-dependent decrease in HaCaT cell viability was previously reported in HaCaT cells exposed to H 2 O 2 (100-500 μM) for 12 h, by MTT assay, with a 50% cell mortality at the concentration of 350 μM H 2 O 2 (Zhang et al, 2020), whereas a survival rate of about 60% was reported by Park et al (2020) for HaCaT cells exposed to 500 μM H 2 O 2 for 24 h. In our study, the H 2 O 2 cytotoxic effect was also confirmed by microscopic observation, which allowed to assess the presence of apoptotic features and decreased cell density. Similar (Bayati et al, 2011;Farshori et al, 2021;Liao et al, 2022 (Park et al, 2020).…”
Section: Discussionmentioning
confidence: 95%
“…In this study, the antioxidant activity of five SVP polysaccharides was determined in vitro by antioxidant experiments, including the DPPH radial scavenging ability, hydroxyl radial scavenging ability, superoxide anion radical scavenging ability, and reducing ability. These findings further demonstrate that the in vivo biological activity of S. vaninii needs to be further explored in terms of the specific antioxidant indicators SOD and CAT [ 39 ] and the related protein pathway Nrf-2/Keap-1 [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work, we have proven that the main functional components of SBE playing a role in the repair of oxidative damage were polysaccharides, alkaloids, and polyphenols by analysis of the primary constituents of SBE [ 18 ]. Liao [ 38 ] showed that Ischnoderma Resinosum polysaccharides had a strong antioxidant activity to protect injured cells, and the protective effect on cells was dose-dependent.…”
Section: Discussionmentioning
confidence: 99%